THE EFFECT OF POSITIVE THINKING THERAPY ON REDUCING ANXIETY IN UNIVERSITY STUDENTS - Devina Rizki Adhisty Devina; Basyar Mauludi Usiska; Yuniza Eka Putri Larasati; Iin Indriyani; Salsabila Azzahra; Muthmainnah Isnaini (Journal of Islamic Psychology and Behavioral Sciences, 2023)
Anxiety is a condition in which emotions are used to show an emotional response that is not in accordance with the circumstances that cause fear. This study aims to determine the decrease in anxiety in students of the Raden Fatah Islamic State University. The research method used in this research is quantitative with an experimental approach. Experimental research is research that provides treatment to a research sample which then observes the consequences of that treatment on the object of research. The sample of this study were students who experienced high levels of anxiety at the Faculty of Psychology, Raden Fatah Islamic State University, as many as 30 students.